2006
DOI: 10.1534/genetics.106.058990
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution and Functional Diversification in the Members of the Nucleophosmin/Nucleoplasmin Family of Nuclear Chaperones

Abstract: The proper assembly of basic proteins with nucleic acids is a reaction that must be facilitated to prevent protein aggregation and formation of nonspecific nucleoprotein complexes. The proteins that mediate this orderly protein assembly are generally termed molecular (or nuclear) chaperones. The nucleophosmin/ nucleoplasmin (NPM) family of molecular chaperones encompasses members ubiquitously expressed in many somatic tissues (NPM1 and -3) or specific to oocytes and eggs (NPM2). The study of this family of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 67 publications
3
73
1
Order By: Relevance
“…Moreover, immunodepletion and in vitro sperm decondensation experiments demonstrated a sperm decondensation function for these factors. These new findings are different from all previous studies on nucleophosmin/nucleoplasmin, in that nucleophosmin was observed to be expressed in somatic tissues and nucleoplasmin was revealed to be specific to oocytes and eggs in previous studies (Eirin-Lopez et al 2006;Shackleford et al 2001;Wedlich and Dreyer 1988). Our data suggest that Cag-nucleophosmin and Ca-nucleophosmin are nucleophosmin homologs but share expressional and functional commonalities with nucleoplasmin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, immunodepletion and in vitro sperm decondensation experiments demonstrated a sperm decondensation function for these factors. These new findings are different from all previous studies on nucleophosmin/nucleoplasmin, in that nucleophosmin was observed to be expressed in somatic tissues and nucleoplasmin was revealed to be specific to oocytes and eggs in previous studies (Eirin-Lopez et al 2006;Shackleford et al 2001;Wedlich and Dreyer 1988). Our data suggest that Cag-nucleophosmin and Ca-nucleophosmin are nucleophosmin homologs but share expressional and functional commonalities with nucleoplasmin.…”
Section: Discussioncontrasting
confidence: 99%
“…Their molecules contain acidic domains, multiple potential phosphorylation sites, and a putative nuclear localization signal (NLS) (Eirin-Lopez et al 2006), and their functions are multiple and diverse (Burns et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal structured domain mediates oligomerization and protein chaperone activity and contains two putative nuclear export signals (15). The central region, important for interactions with histones (25), is disordered (SI Appendix, Fig. S1A) and highly acidic, and contains a bipartite nuclear localization signal (15).…”
Section: Significancementioning
confidence: 99%
“…S1A) and highly acidic, and contains a bipartite nuclear localization signal (15). Last, the C-terminal domain, which evolved later and is not conserved in other members of the nucleoplasmin family (25), folds into a three-helix bundle (26,27), contains a nucleolar localization signal, and binds to nucleic acids (28). The NPM1 primary structure is highly conserved among mammals and amphibians (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…The nucleophosmin/nucleoplasmin family of histone chaperones is ubiquitously represented throughout the animal kingdom (4,12) and includes the following four main groups: nucleophosmin (NPM1), nucleoplasmin (NPM2 or NP), nucleoplasmin-like (NPM-like), and NPM3. All of them share similarities in their amino acid sequence.…”
Section: Nucleoplasmin (Npmentioning
confidence: 99%